The Heme Oxygenase System Suppresses Perirenal Visceral Adiposity, Abates Renal Inflammation and Ameliorates Diabetic Nephropathy in Zucker Diabetic Fatty Rats - Ndisang, Joseph Fomusi; Jadhav, Ashok; Mishra, Manish (PLOS ONE, 2014)
The growing incidence of chronic kidney disease remains a global health problem. Obesity is a major risk factor for type-2 diabetes and renal impairment. Perirenal adiposity, by virtue of its anatomical proximity to the kidneys may cause kidney disease through paracrine mechanisms that include increased production of inflammatory cytokines. Although heme-oxygenase (HO) is cytoprotective, its effects on perirenal adiposity and diabetic nephropathy in Zucker-diabetic fatty rats (ZDFs) remains largely unclear. Upregulating the HO-system with hemin normalised glycemia, reduced perirenal adiposity and suppressed several pro-inflammatory/oxidative mediators in perirenal fat including macrophage-inflammatory-protein-1α (MIP-1α), endothelin (ET-1), 8-isoprostane, TNF-α, IL-6 and IL-1β. Furthermore, hemin reduced ED1, a marker of pro-inflammatory macrophage-M1-phenotype, but interestingly, enhanced markers associated with anti-inflammatory M2-phenotype such as ED2, CD206 and IL-10, suggesting that hemin selectively modulates macrophage polarization towards the anti-inflammatory M2-phenotype. These effects were accompanied by increased adiponectin, HO-1, HO-activity, atrial-natriuretic peptide (ANP), and its surrogate marker, urinary-cGMP. Furthermore, hemin reduced renal histological lesions and abated pro-fibrotic/extracellular-matrix proteins like collagen and fibronectin that deplete nephrin, an important transmembrane protein which forms the scaffolding of the podocyte slit-diaphragm allowing ions to filter but not massive excretion of proteins, hence proteinuria. Correspondingly, hemin increased nephrin expression in ZDFs, reduced markers of renal damage including, albuminuria/proteinuria, but increased creatinine-clearance, suggesting improved renal function. Conversely, the HO-blocker, stannous-mesoporphyrin nullified the hemin effects, aggravating glucose metabolism, and exacerbating renal injury and function. The hemin effects were less-pronounced in Zucker-lean controls with healthy status, suggesting greater selectivity of HO in ZDFs with disease. We conclude that the concomitant reduction of pro-inflammatory/oxidative mediators, macrophage infiltration and profibrotic/extracellular-matrix proteins, coupled to increased nephrin, adiponectin, ANP, cGMP and creatinine clearance may account for improved renal function in hemin-treated ZDFs. These findings suggest that HO-inducers like hemin may be explored against the co-morbidity of perirenal adiposity and diabetic nephropathy.